Processing of Crispy Chicken and Studying Its Quality Properties - Al – Ani, Ibtihal (Iraqi Journal of Science, 2024)
This investigation was carried out to examine the Processing and effect of addition of different spices on the sensory and microbial properties of the Crispy Chicken . The results revealed than that of treatments 1 (without spices control) , 3 (anise ) , 4 (Thyme) , 5 (curry) , 6 (black Pepper) , 7 ( ginger) and 10 ( garlic ) gined higher score of overall acceptance than treatment 8 ( carnation ) . Did not significant difference of overall acceptance , between treatments 1 , 2 ( black seed ) , 3 , 4 , 5 , 6 , 7 , 9 ( onion ) and 10 and between treatments 2 , 8 and 9 . In regards with microbial tests showed aerobic bacteria highest numbers than adding 2, which amounted to more than 300 the unit cell bacterial cfu / ml and less numbers than adding, which amounted to 6 1 cfu / ml . While not showed bacteria, molds and yeasts than adding 5 and 8 after stored at -18 ° C for 3 days and dissolution at 30-32 º C for two hours and incubation at 37 ºC for 24 hours . And aerobic bacteria appeared the highest numbers than adding 9, which amounted to 6 cfu / ml and less numbers than adding 6, which amounted to 1 cfu/ml . While aerobic bacteria does not appeared than adding 1, 3, 4, 5, 7, 8 and 10 after storaed at – 18º C for 30 days and dissolution at 20-22 º C for two hours and incubation at 37 º C for 24 hours . While after incubation at 37 º C for 48 hours aerobic bacteria appeared the highest numbers than adding 2, which amounted to 350 cfu / ml and less numbers than adding 3, which amounted to 1 cfu / ml , Did not show aerobic bacteria than adding 1 . And appeared aerobic bacteria than adding 1 and 2 which amounted large and prepared by the few than adding 4, which amounted to 2 cfu / ml, while not showed aerobic bacteria in other adding after storaed at -18 º C for 2 months and dissolution at 16 - 18 ºC for two hours and incubation 37 º C for 24 hours. While increased growth of aerobic bacteria than adding 6, 7 and 8, which reached numbers 1, 3, and 1 cfu / ml . While aerobic bacteria does not appeared than adding which amounted 3, 9, and 10, after 48 hours of incubation at 37 ºC . As for the bacteria coliforms did not appeared in all adding during the phases storaed except addition 1 which amounted to 1 cfu / ml after storaed at – 18º C for 30 days and dissolution at 20-22 º C for two hours and incubation for 48 hours in 37 º C .